Diagenetic alterations and deep high-quality reservoirs within deltaic distributary channel facies: a case study from the Permian Shihezi formation in the Hongde area, southwestern Ordos basin, China - Wu, Xiaoming; Shen, Zhicheng; Bao, Yanxin; Wang, Weilin; Yan, Zhandong; Wang, Bo; Zheng, Xiaoyin; Dou, Luxing; Wen, Zhigang (Frontiers in Earth Science, 2024)
Deep tight gas reservoirs are considered important hydrocarbon exploration targets. High-quality reservoir prediction is critical for successfully exploring and developing deeply buried tight sandstone gas. Previous research has found that the reservoir quality of deeply buried tight sandstones is controlled by diagenesis and sedimentary facies. However, the variation of diagenetic alterations in different facies is still poorly studied on deltaic tight gas sandstone. In this study, core analysis, wireline log data, and 3D seismic were studied for the characterization of diagenetic alterations and sedimentary facies. The tight sandstones were formed in braided river delta deposits. Gravel-bearing coarse-grained sandstone facies and cross-bedded sandstone facies developed in tight sandstones. The Gravel-bearing coarse-grained sandstone is formed in the mid-channel bar of deltaic distributary channels. The major diagenetic processes developed in the tight sandstone include compaction, cementation, and dissolution. Constructive diagenesis can generate secondary pores, mainly including dissolution and kaolinite metasomatism, which can effectively improve reservoir physical properties. Through the diagenesis alterations linked to different lithofacies in cored wells, there are obvious diagenesis variations in different lithofacies. Despite strong compaction, the reservoirs in coarse sandstone facies have developed internal dissolution. After compaction, cementation, and dissolution to increase porosity, the reservoir retains intergranular and secondary pores and forms relatively high-quality reservoirs. The fine sandstone facies with cross-bedding are strongly compacted, with internal ductile particles being compacted and deformed, and the particle orientation is clearly arranged. The reservoir is tight, and the development of dissolution in the reservoir is weak, resulting in poor reservoir quality. In addition, reservoirs located at the interface between sandstone and mudstone are often affected by diagenesis, resulting in the development of calcareous cementation, leading to poor reservoir quality. Therefore, high-quality reservoirs are mostly distributed in coarse sand lithofacies, mainly distributed in the mid-channel bar of distributary channel deposits. Sedimentary facies control the original physical properties of the reservoir with different content and texture; the quality of the original reservoir is subject to diagenetic alteration in different ways. The points in this study could offer insights better to predict deep tight reservoir quality in continental basins.